Efficient improvement for dissociation behavior and thermal decomposition of manganese ore by microwave calcination. (1st July 2020) - Li, Kangqiang; Chen, Jin; Peng, Jinhui; Omran, Mamdouh; Chen, Guo
Abstract: Traditional smelting process of manganese ore was plagued with high consume of power and coke, and spraying and slag turning accidents caused by violent decomposition of carbonates and manganese oxides in manganese ore. In the present work, the thermal decomposition mechanism and phase structures of manganese ore were systematically investigated, calcined through microwave calcination approach and characterized by XRD, SEM and EDAX. Results indicated that microwave calcination had a significantly better effect than conventional calcination for manganese ore. An increase in calcination temperature was found to present a more profound effect than calcination duration. The optimum calcination temperature was identified to be 950 °C, with the calcination duration being 30 min, and manganese ore grade increased from initial 30% to 39%–42%, with the pulverization ratio being 8%–9%. Peak intensities of Mn3 O4 phase enhanced with calcination temperature increasing, and irregular cracks and pits appeared on the surface of the microwave calcined manganese ore. Meanwhile, the feasibility of decomposition reactions of manganese ore at the considered temperature regime was confirmed by thermodynamics analysis. The upgrading and modified manganese ore by microwave calcination can realize the direct smelting of the concentrate. The work proposes an efficient calcination idea for manganese ore by microwave calcination. Highlights: The main highlights of this work are as follows. Exploration of dissociation behavior and thermal decomposition of manganese ore. Microwaves as energy source to enhance dissociation behavior of manganese ore. Manganese ore modified by microwave calcination meet industrial furnace standards. Irregular cracks and pits appeared on surface of microwave calcined manganese ore.